PEMBERDAYAAN KELOMPOK POKDARWIS DESA BUKIT JANGKRIK LEWAT BUDIDAYA LEBAH TRIGONA DAN KEBUN PAKAN - I Putu Eka Indrawan; Ni Nyoman Parmithi; Ayu Aprilyana Kusuma Dewi; Luh Putu Risma Noviana (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
The development of Trigona honey bee farming by the Pokdarwis Group in Bukit Jangkrik Village, Gianyar, is still in its early stages toward becoming a productive economic activity. However, several fundamental challenges, such as limited availability of bee feed and insufficient knowledge about honey harvesting techniques, have resulted in low quality and quantity of production. To address these issues, a community service program was conducted from February to May 2025, involving 20 participants from the management and members of the Pokdarwis group. The solutions offered include knowledge and technology transfer through training on Trigona bee feed plant species and demonstration planting on demonstration plots (demplots). The program aims to enrich bee forage sources with sustainable nectar and pollen-producing plant species while enhancing partners' understanding of better honey production strategies. Bukit Jangkrik Village itself possesses ideal ecological potential for Trigona bee development, thereby strongly supporting the program's success. Following the activities, a significant increase in participants' knowledge was observed, with 100% of participants understanding the types of Trigona bee forage plants. This achievement demonstrates that the program has had a tangible impact in enhancing partners' capacity toward productive economic development. Moving forward, this progress is expected to serve as a strong foundation for promoting the sustainability of Trigona honey-based ecotourism and improving community well-being through the utilization of locally available, competitive resources.